Prenatal diagnosis of Prader–Willi syndrome via maternal UPD15 with placental mosaicism: incidental discovery of fetal DMD carrier status - Ye, Yanchou; Fu, Yiman; Zhang, Zhechao; Ning, Haofeng; Tao, Fangchao; Wang, Xiaonan; Fang, Qun; Chen, Zheng; Hao, Xiulan (Frontiers in Genetics, 2025)
BackgroundPrader–Willi syndrome (PWS) represents a paradigm of genomic imprinting disorders. Given the severe lifelong complications of PWS, prenatal diagnosis is crucial for early intervention and genetic counseling.MethodsNoninvasive prenatal testing (NIPT) indicated a high risk for fetal trisomy 15 (T15), prompting confirmatory invasive testing. Amniocentesis was performed, and amniotic fluid was analyzed by karyotyping, chromosomal microarray analysis (CMA), trio-based whole-exome sequencing (trio-WES), and short tandem repeat (STR) linkage analysis to investigate the genetic etiology. Post-termination, placental tissue was analyzed by copy number variant sequencing (CNVseq) to evaluate potential mosaicism.ResultsNIPT indicated a suspected T15 (Z-score: 16.4). Subsequent invasive testing confirmed the following: a 13.16 Mb region of homozygosity on chromosome 15q25.1q26.1 and a 273 kb Duchenne muscular dystrophy (DMD) gene deletion on chromosome Xp21.1, both identified by CMA. Trio-WES and STR linkage analysis revealed maternal segmental uniparental disomy of chromosome 15 (UPD15), confirming the genetic basis of PWS. Post-termination, CNVseq further demonstrated confined placental mosaicism (CPM) for T15.ConclusionWhen NIPT suggests a high risk of T15, clinicians should maintain a high suspicion for the “trisomy rescue” mechanism, where an initially trisomic zygote undergoes mitotic correction, ultimately forming UPD15 with CPM. The potential discordance between NIPT and the actual fetal genetic status necessitates definitive prenatal diagnosis, which has critical implications for subsequent pregnancy management. Therefore, the concomitant findings of PWS and DMD carrier status require comprehensive prognostic evaluation and recurrence risk assessment.